2008
DOI: 10.1039/b716104b
|View full text |Cite
|
Sign up to set email alerts
|

Laser flash photolysis study of the triplet reactivity of β-lapachones

Abstract: The photochemical reactivity of beta-lapachone (1), nor-beta-lapachone (2) and beta-lapachone 3-sulfonic acid (3) has been examined by laser flash photolysis. Excitation (lambda = 266 nm) of degassed solutions of , in acetonitrile or dichloromethane, resulted in the formation of detectable transients with absorption maxima at 300, 380 and 650 nm. These transients, with lifetimes of 5.0 micros, were quenched by beta-carotene at a diffusion-controlled rate constant and assigned to the triplet excited states of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
18
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
9
18
0
2
Order By: Relevance
“…This could be related to the fact that one of the proposed mechanisms for the cytotoxic action of quinones involves the alkylation of thiol groups on the thiol-containing enzymes. 44 This same mechanism could be operating in the quenching of the triplet excited state of b-lapachone-3-sulfonic acid, which would explain the lack of observation of the semiquinone radical.As previously reported by our group, triplet 1 has pp* configuration 23 The Photochemical Reactivity of Triplet b-Lapachone-3-sulfonic Acid J. Braz. Chem.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…This could be related to the fact that one of the proposed mechanisms for the cytotoxic action of quinones involves the alkylation of thiol groups on the thiol-containing enzymes. 44 This same mechanism could be operating in the quenching of the triplet excited state of b-lapachone-3-sulfonic acid, which would explain the lack of observation of the semiquinone radical.As previously reported by our group, triplet 1 has pp* configuration 23 The Photochemical Reactivity of Triplet b-Lapachone-3-sulfonic Acid J. Braz. Chem.…”
supporting
confidence: 57%
“…6, 2010 topoisomerase IIa-mediated DNA breaks, 20 and inhibition of poly(ADP-ribose) polymerase-1. 21 More recently, Boothman and co-workers 23 have clearly demonstrated that b-lapachone, an ortho-quinone, activates a novel apoptotic response in a number of cell lines. It was shown that the enzyme NAD(P)H:quinone oxidoreductase (NQO1) substantially enhances the toxicity of b-lapachone in a number of tumor types (i.e., breast, pancreatic, colon, prostate and lung) and during neoplastic transformation.…”
mentioning
confidence: 99%
“…This mechanism, shown in Scheme 1, involves an initial electron transfer from the phenol to the excited ketone, through an intermediate exciplex, followed by an ultrafast proton transfer, which ultimately results in the formation of the radical pair ketyl/ phenoxyl. [1][2][3][4][5][6][7][8] In support to this mechanism, Figure 4 shows a representative spectrum obtained after laser irradiation of a deoxygenated solution of thiochromanone (1) acetonitrile. In this spectrum the absorptions relative to triplet 1 were substituted for new ones in the 340-440 nm region, which can be associated to a mixture of the ketyl radical 2 derived from the thiochromanone triplet, as well as to the 4-methoxyphenoxyl radical, which shows absorption at 405 nm 41 (Scheme 1).…”
Section: Resultsmentioning
confidence: 94%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The mechanism for this process is now well established and involves the initial formation of a hydrogen-bonded exciplex in the triplet excited state, followed by electron transfer and, subsequently, an ultrafast proton transfer. 4,[9][10][11][12][13][14][15][16] DFT calculations clearly showed that for the triplet complex (exciplex) ketone-phenol the hydrogen transfer is predominantly occurring.…”
Section: Introductionmentioning
confidence: 99%
“…36 The results showed that formaldehyde, acetone, and cyclohexanone have a high grafting efficiency, especially acetone which gives the highest grafting efficiency. The reaction of phenols as efficient inhibitors implies two facts: the H atoms in PhOH have a high reactivity to readily be abstracted [37][38][39] and the formed PhOÁradicals have a strong ability to scavenge carbon-centered chain radicals. 40 In this work, acetone as photoinitiator and different phenols [including 4-hydroxylbenzene sulfonic acid (HBSA), p-aminophenol, tyramine, and 4-hydroxythiophenol and tyrosine] with a para substituent XR (denoted XRPhOH) as the reactants were proposed to incorporate a broad range of functional X groups with an R spacer onto the polymeric surface as illustrated in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%